Research on key factors and decision-making in the adaptive reuse of industrial buildings as hotels in third-tier cities in northern China: the large machinery maintenance workshop in Hohhot - Gong, Zehong; Si, Yang; Zhang, Qiuling; Rong, Xinyi; Lyv, Jiaqing (Frontiers in Sustainable Cities, 2025)
With the acceleration of urbanization and industrial upgrading in China, vacant industrial buildings in many third-tier cities have gradually emerged as significant resources, playing a crucial role in urban carbon reduction and cultural continuity. This study identified the influencing factors using the fuzzy hierarchical analysis method and ranked them in descending order: market, sustainability, economy, building physics, legal policy, location environment, and public interest. Through expert discussions, it was further clarified that: (1) the adaptive reuse of industrial buildings should prioritize functional transformation, and an accurate customer profile is an important basis for decision-making; (2) green building renovations can leverage government policy benefits while enhancing the competitiveness of the hotel market; and (3) policies and the local environment are not the primary influencing factors in third-tier cities in northern China—which contrasts with findings from previous studies. The research results provide a valuable reference for the adaptive reuse of industrial buildings in third-tier cities of developing countries and offer stakeholders better decision-making insights regarding transformation functions.